Guidance and Counseling Services in Addressing Dating Issues Among Students of SMPN 11 Kupang City - Takene, Hilda Kurniaty; Elinda, Maria (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to understand the implementation of guidance and counseling services in addressing dating cases at SMPN 11 Kota Kupang. Using a descriptive qualitative method with structured interviews, the study found that student dating has an impact on decreased concentration in learning due to a lack of attention from the family. Guidance counselors comprehensively implement information services, individual counseling, and group counseling. The effectiveness of the handling depends on the collaboration between guidance counselors, homeroom teachers, and parents. In conclusion, a multilevel approach with collaboration from all parties is the key to successfully handling student dating cases in junior high schools.